Peningkatan Budaya Literasi Membaca Pada Siswa Kelas 1 di SD Negeri 03 Kembang Tanjung Melalui Media Pop Up Book - Hartono; Ridha Nurjanah; Indah Ilya Mustofa; Desi Romadhon; Tia Safitri; Zikri Zulkarnain (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2023)
This community service activity is part of the KKN UMKO Transfer Knowledge activities for Muhammadiyah University Kotabumi Students which was carried out on January 31 2023 – March 2 2023 in Kembang Tanjung Village, South Abung District, North Lampung Regency, Lampung. This KKN activity is carried out by lecturers and students to the community, especially in the field of education in order to improve a culture of reading literacy in elementary school students. So the solution is to make interesting reading media, namely pop up book media. The method of implementing this activity starts with making reading media, namely pop up books. Furthermore, students introduced pop up book reading media to elementary school students and asked students to read stories that had been made through pop up book reading media. After this interesting pop up book reading media, it is hoped that elementary school students will be more diligent in reading so that there are no more elementary school students who cannot read.